FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN MEDIA CYBER EXTENTION OLEH PENYULUH PERTANIAN DI KOTA SUNGAI PENUH - Dermawan Putra; Sri Wahyuni; Zul Irfan (Agros Journal of Agriculture Science, 2023)
Agricultural extension is an important and strategic activity that cannot be separated from development in the agricultural sector. Therefore, extension workers must be able to keep up with the development of information through the use of information and communication technology media, namely cyber extension media. Based on observations, it is known that in supporting extension activities in Sungai Penuh City, extension workers have utilized cyber extension media as a means of adding information and increasing their knowledge but their utilization is not optimal. The purpose of this research is to describe how the utilization of cyber extension media by agricultural extension workers and analyze what factors affect the utilization of cyber extension media by agricultural extension workers in Sungai Penuh City. This research method is descriptive quantitative. The sample was taken by census, which amounted to 63 respondents. The results showed that the utilization of cyber extension media by agricultural extension workers in Sungai Penuh City was still low as seen from the frequency of access to cyber extension media, namely 52 extension workers (82.5%) (3-14 times / month) and the duration of access to cyber extension media as many as 51 extension workers (81%) (1-6.8 hours / month). Then the factors that influence the utilization of cyber extension media by agricultural extension workers in Sungai Penuh City are age, motivation of extension workers in increasing knowledge and insight and training. INTISARIPenyuluhan pertanian merupakan kegiatan penting dan strategis yang tidak dapat dipisahkan dari pembangunan di sektor pertanian. Oleh karena itu, penyuluh harus mampu mengikuti perkembangan informasi melalui pemanfaatan media teknologi informasi dan komunikasi yaitu media cyber extension. Berdasarkan observasi diketahui bahwa dalam menunjang kegiatan penyuluhan di Kota Sungai Penuh, penyuluh sudah memanfaatkan media cyber extension sebagai sarana menambah informasi dan meningkatkan pengetahuannya namun pemanfaatannya belum optimal. Tujuan peneilitian ini adalah untuk mendeskripsikan bagaimana pemanfataan media cyber extention  oleh  penyuluh pertanian serta menganalisis faktor-faktor apa saja yang mempengaruhi pemanfaaatan media cyber extension oleh penyuluh pertanian di Kota Sungai Penuh. Metode penelitian ini adalah deskriptif kuantitatif. Sampel diambil secara sensus yaitu berjumlah 63 orang responden. Hasil penelitian didapat bahwa pemanfaatan media cyber extension oleh penyuluh pertanian di Kota Sungai Penuh masih rendah terlihat dari frekuensi akses media cyber extension yaitu sebanyak 52 penyuluh (82,5%) (3-14 kali/3bulan) dan durasi akses media cyber extension sebanyak 51 penyuluh (81%) (1-6,8 Jam/3bulan). Kemudian faktor-faktor yang berpengaruh terhadap pemanfaatan media cyber extension oleh penyuluh pertanian di Kota Sungai Penuh adalah umur, motivasi penyuluh dalam meningkatkan pengetahuan dan wawasan serta pelatihan.